2018
DOI: 10.1093/aob/mcy164
|View full text |Cite
|
Sign up to set email alerts
|

Could vesicular transport of Na+ and Cl– be a feature of salt tolerance in halophytes?

Abstract: There is strong evidence in favour of vesicular transport in plants and circumstantial evidence in favour of the movement of ions in vesicles. Estimated rates of vesicle turnover could account for ion transport at the lower reported fluxes (around 20 nmol m-2 s-1), but the higher fluxes may require vesicles of the order of 1 μm or more in diameter. The very high fluxes reported in some salt glands might be an artefact of the way they were measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 229 publications
(256 reference statements)
1
39
0
1
Order By: Relevance
“…The vacuole appears as a flexible bubble, widening and narrowing the space between the tonoplast and plasma membrane (L€ ofke et al, 2015). This provides the opportunity for direct contact of the two membranes and the possibility of a direct 'shunt' for ions to enter the vacuole either without crossing through the cytosol or crossing via a cytosolic micro domain with different conditions (Flowers et al, 2018).…”
Section: Membrane Dynamics Avoid Transmembrane Crossingsmentioning
confidence: 99%
“…The vacuole appears as a flexible bubble, widening and narrowing the space between the tonoplast and plasma membrane (L€ ofke et al, 2015). This provides the opportunity for direct contact of the two membranes and the possibility of a direct 'shunt' for ions to enter the vacuole either without crossing through the cytosol or crossing via a cytosolic micro domain with different conditions (Flowers et al, 2018).…”
Section: Membrane Dynamics Avoid Transmembrane Crossingsmentioning
confidence: 99%
“…Energy consumption would increase if the Na + is transported by the cell-to-cell route and crosses multiple membranes. Alternatively Na + could be moved inside small vesicular compartments between cells in the symplasm and via plasmodesmata, or via extracellular vesicles transported in the vasculature (Rutter & Innes, 2017;Flowers et al, 2018) thereby minimising membrane crossing steps.…”
Section: Costs Of Ion Transport Across Rootsmentioning
confidence: 99%
“…When L. bicolor leaves were treated with brefeldin A, a vesicle secretion inhibitor, the secretion rate of the salt glands was severely inhibited (Feng et al, 2015). Similarly, Flowers et al (2019) reported results that supported the hypothesis that vesicle transport plays a key role in salt gland secretion, although they also indicated that transporters may be simultaneously involved. Vesicle transport consumes less energy than transport proteins, and ions can accumulate to a high concentration in the vesicles (Lu et al, 2020).…”
Section: Resultsmentioning
confidence: 81%